Terminating the pregnancy of a braindead mother: Does a fetus have a right to life The law in South Africa - David McQuoid-Mason (South African Journal of Bioethics and Law, 2014)
In the recent Texas case of Munoz v John Peter Smith Hospital, a husband obtained a court order for the removal of life support from his brain dead pregnant wife whose body was decaying, after a hospital tried to keep her on â€˜life supportâ€™ until the foetus was born. The question is whether a South African court would have issued a similar order but for different reasons. The answer is probably yes because in this country a foetus has not legal rights until it is born. Unlawfully subjecting a dead pregnant women to â€˜life supportâ€™ measures to keep a foetus alive, where the deceased has not made a will to that effect, and against the wishes of the family, may result in a criminal charge of a violating a corpse. Â